GONDANG SITOLUPULUTOLU PADA UPACARA ADAT SAUR MATUA MASYARAKAT BATAK TOBA SILAHISABUNGAN - Sopandu Manurung; Gabriel Roosmargo Lono Lastoro Simatupang; Aton Rustandi Mulyana (Institut Seni Indonesia Surakarta, 2022)
Gondang Sitolupulutolu is a gondang ensemble that can only be found in the Toba Batak community. They are Silalahisabungan clan group. Gondang sitolupulutolu is very important in the Silahisabungan community because it can not be separeted from the traditional ceremonies. This study aims to determine how the use and function of the gondang sitolupulutolu in one of the traditional ceremonies of the Silahisabungan community, namely saur matua. This study use a qualitative method. Alan P. Meriam’s (1964) theory of use and function was chosen to see the use and function of the gondang sitolupulutolu. The results showed that the Gondang Sitolupulutolu was used at the opening ceremony during the manortor (ceremonial dance) and at the end of ceremony (closing ceremony). While the function of the gondang sitolupulutolu at the traditional ceremony of Saur Matua is as an expression of joy and sorrow, as entertainment, as a means of communication to convey prayers to God, as a symbol, and as a validation of the Saur Matua traditional ceremony.